Functional Roles of a Ca 2+ -Activated K + Channel in Atrioventricular Nodes - Qian Zhang; Valeriy Timofeyev; Ling Lü; Ning Li; Anil Singapuri; Melissa Long; Chris T. Bond; John P. Adelman; Nipavan Chiamvimonvat (2007)
Since the first description of the anatomical atrioventricular nodes (AVNs), a large number of studies have provided insights into the heterogeneity of the structure as well as a repertoire of ion channel proteins that govern this complex conduction pathway between the atria and ventricles. These studies have revealed the intricate organization of multiple nodal and nodal-like myocytes contributing to the unique electrophysiology of the AVN in health and diseases. On the other hand, information regarding the contribution of specific ion channels to the function of the AVN remains incomplete. We reason that the identification of AVN-specific ion channels may provide a more direct and rational design of therapeutic target in the control of AVN conduction in atrial flutter/fibrillation, one of the most common arrhythmias seen clinically. In this study, we took advantage of 2 genetically altered mouse models with overexpression or null mutation of 1 of a small conductance Ca2+-activated K+ channel isoform, SK2 channel, and demonstrated robust phenotypes of AVN dysfunction in these experimental models. Overexpression of SK2 channels results in the shortening of the spontaneous action potentials of the AVN cells and an increase in the firing frequency. On the other hand, ablation of the SK2 channel results in the opposite effects on the spontaneous action potentials of the AVN. Furthermore, we directly documented the expression of SK2 channel in mouse AVN using multiple techniques. The new insights may have important implications in providing novel drug targets for the modification of AVN conduction in the treatment of atrial arrhythmias.